Role of microRNA in microglial phenotype during the progression of Alzheimer’s disease - Monteiro, Mafalda Aurélio (2018)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2016